Perspectives of interpretation of Meaning in English - Adegbite, Wale (2014)
It is not unusual that 'meaning' presents a problem of definition to language scholars. Like many other concepts, meaning is either a vague or an ambiguous term, depending on the way one looks at it. As far back as 1923, Ogden and Richards gave a representative list of sixteen main definitions which, according to them, "reputable students of meaning have favoured". Recent studies may have observed some considerable overlaps in most of these definitions, but the multifarious types, perspectives and interpretations of meanings are still with us.